Surfactin: A Quorum-Sensing Signal Molecule to Relieve CCR in Bacillus amyloliquefaciens - Chen, Bing; Wen, Jiahong; Zhao, Xiuyun; Ding, Jia; Qi, Gaofu (Frontiers in Microbiology, 2020)
Bacillus utilize preferred sugars such as glucose over other carbon sources due to catabolite repression (CCR), but how to relieve CCR is still unknown. Surfactin is a small signal molecule to regulate quorum-sensing response (QS) such as biofilm formation and sporulation in Bacillus. Here, the srfA operon for synthesis of surfactin was mutated for blocking production of surfactin in B. amyloliquefaciens. The mutant strain was found with impaired biofilm formation and sporulation that could be restored by addition with surfactin, indicating surfactin was also a QS signal molecule in B. amyloliquefaciens. Unexpectedly, mutation of srfA led to death at the start of exponential growth although nutrients were still enough to support the bacterial growth during this period. Analysis of transcriptomes found the srfA-mutated strain could not relieve CCR to use non-preferred carbon sources after glucose exhaustion due to deficiency of surfactin. This was further verified by the fact that addition with glucose could dramatically restore the impaired growth of srfA mutant strain, and addition with surfactin could improve the enzymes activity (e.g. glucanase and α-amylase) to use non-preferred carbon sources for restoring growth. CcpA was involved in the role of surfactin to relieve CCR because knockout of ccpA could restore the ability to use non-preferred carbon sources in the srfA mutant strain. Our findings firstly verified that surfactin is a signal molecule to relive CCR in B. amyloliquefaciens. By surfactin, QS is tightly linked with CCR to counter carbon source limitation in the natural environment.